2000
DOI: 10.1016/s0045-6535(00)00039-4
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts as a model for assessing the toxicity of the fungicides Penconazol, Cymoxanil and Dichlofluanid

Abstract: In the present work the sensitivity of yeast strains of Kluyveromyces marxianus, Pichia anomala, Candida utilis, Schizosaccharomyces pombe and Saccharomyces cerevisiae, to the fungicides cymoxanil, penconazol, and dichlo¯ua-nid, was evaluated. Dichlo¯uanid induced the most negative eects, whereas penconazol in general was not very toxic. Overall, our results show that the parameters IC 50 for speci®c respiration rates of C. utilis and S. cerevisiae and C D for cell viability of S. cerevisiae can be applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 8 publications
2
27
0
Order By: Relevance
“…Comitini and Ciani (2008) noticed a drastic reduction in the yeast population caused by fungicides. Saccharomyces cerevisiae exhibited the highest sensitivity to some fungicides (Ribeiro et al, 2000). Our results show lower incidence of this species on leaves of fruit trees in comparison to wood trees, which could be affected by the chemical spraying of fruit trees.…”
Section: Resultsmentioning
confidence: 59%
“…Comitini and Ciani (2008) noticed a drastic reduction in the yeast population caused by fungicides. Saccharomyces cerevisiae exhibited the highest sensitivity to some fungicides (Ribeiro et al, 2000). Our results show lower incidence of this species on leaves of fruit trees in comparison to wood trees, which could be affected by the chemical spraying of fruit trees.…”
Section: Resultsmentioning
confidence: 59%
“…For example, yeast cells have contributed in recent years to clarify the role reactive oxygen species (ROS) in diseases such as amyotrophic lateral sclerosis or Friedereich's ataxia (Costa & Moradas-Ferreira, 2001). Studies on the evaluation of pesticides still depend extensively on the use of animals, but in the last years several publications have dealt with the development and appropriateness of alternative methods for assessing toxicity, that do not depend on animal utilization but explore the use of rapid and cost-effective alternatives (Ribeiro et al, 2000).…”
Section: Yeast As An Eukaryotic Model Systemmentioning
confidence: 99%
“…Razmovski and Pucarevic [17,18] showed that flutriafol (a fungicide) decreased the protein and phosphorus cell content, as well as total ribonucleic acids, enzymatic activity (pyruvate carboxylase and isocitrate lyase), and respiration quotient of S. cerevisiae. Finally, Ribeiro et al [9] also observed that S. cerevisiae specific respiration rates were reduced by other pesticides (Penconazol, Cymoxanil, and Dichlofluanid), showing that pesticides inhibit the yeast's respiratory metabolism.…”
Section: Introductionmentioning
confidence: 96%
“…However, the majority of the existing microbial toxicity tests are not sensitive enough to detect low concentrations of pollutants [8]. Eukaryotes such as yeasts are potentially good models for assessing toxicity [9] as they are easy to maintain and culture under controlled conditions, thus avoiding the variability issues found with more complex organisms [10].…”
Section: Introductionmentioning
confidence: 99%